Development of self-education skills and professional core competencies among university students in continuing education - Vasilieva, N. G. (Problems of Engineer-Pedagogical Education, 2018)
The article considers peculiar features of the development of self-education skills and professional core competencies in the process of continuing education. The development of an individual as an active participant and a gradual transition from upbringing and education to self-education and self-upbringing are markers of the present time and some of the main tasks of the higher school. It is vitally important to provide students with basic knowledge that will allow them to get further education and acquire skills continuously throughout their lives. Self-education of the engineer-pedagogue is regarded as a complex, multifaceted, lifelong, creative process, the results of which have a double meaning: improvement and development of the professional activity of the teacher and qualitative changes in his or her personality. Self-education of the higher school teacher becomes a prerequisite for his or her personal and professional growth, if this activity is conceptually substantiated and carried out through creative educational activities as a permanent process whose content is directed at self-knowledge and self-improvement as a pedagogue, human being, individual and individuality, and at mastering innovative educational ideas and technologies.